Prevalence and characterization of plasmid-mediated quinolone resistance genes in Proteus species isolated from different patients - Dalia G. Ali; Gamal F. M. Gad; Osman A. O. Ismail; Hala R. Ahmed; Reham A. Ibrahem (Novel Research in Microbiology Journal)
Proteus spp. are widely distributed opportunistic pathogens that can cause various human infections. A total of 361 clinical specimens were obtained from patients who were attending to different hospitals in El-Minia governorate, Egypt. Approximately 23 % of the samples belong to Proteus spp. isolates which were obtained from various clinical sources. After biochemical identification, 42.1 % of isolates were found to belong to Proteus vulgaris and 57.8 % to P. mirabilis. The urine samples collected from catheterized patients represented 32.6 % of all the clinical specimens, and the majority of the recorded isolates were Proteus spp. The antibacterial sensitivity of the Proteus spp. was examined using 16 different antibiotics from various families. The most effective antibiotics were Amikacin; Levofloxacin, and Meropenem, recording 68.6 %, 66.2 %, and 62.2 % of the isolates sensitivity to each of these antibiotics, respectively. Using the ureR-based PCR, 48 % of the isolates were identified as P. mirabilis. Moreover, the Qnr genes (i.e., qnrA, qnrB, qnrS, qnrD, and qnrC) and the aac (6')-Ib-cr gene had been identified in 40 % of P. mirabilis isolates. The aims of the study were to investigate the prevalence of Proteus spp. in El-Minia, Egypt; determine the antibacterial susceptibility pattern of these isolates, and characterize the PMQR genes in Proteus spp. Quinolone resistance in P. mirabilis isolates might have been brought on by mechanisms other than qnr and aac (6')-Ib genes. Finally, since Proteus spp. are widespread in the environment; healthcare facilities must uphold stringent sanitation standards to reduce the incidence of the nosocomial infections.